2021
DOI: 10.3389/fonc.2021.553594
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive In Silico Analysis of a Novel Serum Exosome-Derived Competitive Endogenous RNA Network for Constructing a Prognostic Model for Glioblastoma

Abstract: PurposeGlioblastoma (GBM) is one of the most aggressive brain tumors with high mortality, and tumor-derived exosomes provide new insight into the mechanisms of GBM tumorigenesis, metastasis and therapeutic resistance. We aimed to establish an exosome-derived competitive endogenous RNA (ceRNA) network for constructing a prognostic model for GBM.MethodsWe obtained the expression profiles of long noncoding RNAs (lncRNAs), miRNAs, and mRNAs from the GEO and TCGA databases and identified differentially expressed RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Moreover, STEAP3-AS1 caused the expression of its neighboring STEAP3 in a m 6 A modification-dependent manner, which activated Wnt/β-catenin signaling to support CRC progression. Importantly, recent in silico analysis of a serum exosome-derived ceRNA network has identified STEAP3-AS1 as an independent prognostic predictor of glioblastoma and gallbladder cancer [ 48 , 49 ], further proving its clinic value as a promising biomarker for cancers. Therefore, further studies elucidating the functions of secreted STEAP3-AS1 in CRC progression may expand its applications for early detection or prediction of drug response in CRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, STEAP3-AS1 caused the expression of its neighboring STEAP3 in a m 6 A modification-dependent manner, which activated Wnt/β-catenin signaling to support CRC progression. Importantly, recent in silico analysis of a serum exosome-derived ceRNA network has identified STEAP3-AS1 as an independent prognostic predictor of glioblastoma and gallbladder cancer [ 48 , 49 ], further proving its clinic value as a promising biomarker for cancers. Therefore, further studies elucidating the functions of secreted STEAP3-AS1 in CRC progression may expand its applications for early detection or prediction of drug response in CRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…H19 has a potential reference value for glioma remission and immunotherapy. ST3GAL6-AS1 and SOX21-AS1 as protective factors have been reported in cancers, lncRNA ST3GAL6-AS1 overexpression significantly reduces colorectal cancer cell tumorigenesis and metastasis ( 29 ), and lncRNA SOX21-AS1 significantly suppresses tumorigenesis in cervical cancer ( 30 ), oral cancer ( 31 ), and GBM ( 32 ). Relevant literature reports for AL162231.2 , AC002456.1 , and AC006213.5 are sparse.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that GBM with GS-A were characterized by four high-risk lncRNAs ( H19 , HOTAIRM1 , AGAP2-AS1 , and AC002456.1 ) and one high-risk mRNA KRT8 with a low expression level. Among these lncRNAs and mRNAs, lncRNA HOXA transcript antisense RNA myeloid-specific 1 ( HOTAIRM1 ) participates in the reprogramming of chromatin organization and proliferation and metastasis of cancer ( 32 ), which has been found to be highly expressed in a variety of tumors including GBM ( 41 ). LncRNA AGAP2 antisense RNA 1 ( AGAP2-AS1 ), transcribed from a gene located at 12q14.1, a novel cancer-related lncRNA, was dysregulated in cancers ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…STEAP3-AS1 was also identified as a novel, potential prognostic biomarker, and therapeutic target for tongue squamous cell carcinoma (TSCC) [42]. STEAP3-AS1, together with HOTAIR and SOX21-AS1, as the exo-lncRNA signature, was proven to be an independent prognostic factor in glioblastoma (GBM) [43]. MAD2L1, MAD2 mitotic arrest deficient-like 1, is a critical mitotic checkpoint gene.…”
Section: Discussionmentioning
confidence: 99%